2024
DOI: 10.3390/land13030379
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Digital Soil Mapping Approaches in Lowland Areas

Odunayo David Adeniyi,
Hauwa Bature,
Michael Mearker

Abstract: Digital soil mapping (DSM) around the world is mostly conducted in areas with a certain relief characterized by significant heterogeneities in soil-forming factors. However, lowland areas (e.g., plains, low-relief areas), prevalently used for agricultural purposes, might also show a certain variability in soil characteristics. To assess the spatial distribution of soil properties and classes, accurate soil datasets are a prerequisite to facilitate the effective management of agricultural areas. This systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…The study revealed a trend of soil organic matter depleting over time, highlighting the need for soil conservation and restoration actions. With the latest accepted review paper, Adeniyi et al [37], conducted a systematic review of digital soil mapping application in lowland areas, emphasizing the growing recognition of the pivotal role of digital soil mapping in understanding soil properties in agricultural lowlands. These studies collectively demonstrate the capacity of machine learning models to advance our ability to assess spatial distribution of soil properties (e.g., electrical conductivity soil organic carbon content and stocks), thereby providing valuable insights for sustainable land management, agricultural productivity, and environmental conservation strategies.…”
mentioning
confidence: 99%
“…The study revealed a trend of soil organic matter depleting over time, highlighting the need for soil conservation and restoration actions. With the latest accepted review paper, Adeniyi et al [37], conducted a systematic review of digital soil mapping application in lowland areas, emphasizing the growing recognition of the pivotal role of digital soil mapping in understanding soil properties in agricultural lowlands. These studies collectively demonstrate the capacity of machine learning models to advance our ability to assess spatial distribution of soil properties (e.g., electrical conductivity soil organic carbon content and stocks), thereby providing valuable insights for sustainable land management, agricultural productivity, and environmental conservation strategies.…”
mentioning
confidence: 99%